Epitaxial growth of silicon carbide on on-axis silicon carbide substrates using methyltrichlorosilane chemical vapor deposition - Swanson, Kyle (Kansas State University, 2008)
4H-silicon carbide (4H-SiC) is a wide band gap semiconductor with outstanding capabilities for high temperature, high power, and high frequency electronic device applications. Advances in its processing technology have resulted in large micropipe-free single crystals and high speed epitaxial growth on off-axis silicon face substrates. Extraordinarily high growth rates of high quality epitaxial films (>100 [Mu]m per hour) have been achieved, but only on off-axis substrates (misoriented 4° to 8° from the (0001) crystallographic plane). There is a strong incentive to procure an on-axis growth procedure, due to the excessive waste of high quality single crystal associated with wafering off-axis substrates. The purpose of this research was to develop a reliable process for homoepitaxial growth of 4H-SiC on on-axis 4H-SiC. Typically the use of on-axis SiC for epitaxial growth is undesired due to the increased probability of 3C-SiC inclusions and polycrystalline growth. However, it is believed that the presence of chlorine during reaction may reduce the presence of 3C-SiC and improve the quality of the epitaxial film. Therefore homoepitaxial SiC was deposited using methyltrichlorosilane (MTS) and ethane sources with carrier gases consisting of argon-hydrogen mixtures. Ethane was used to increase the C/Si ratio, to aid in the prevention of 3C-SiC, and to help eliminate silicon droplets deposited during epitaxial growth. Deposition occurred in a homemade, quartz, cold wall chemical vapor deposition reactor. Epitaxial films on on-axis 4H-SiC were deposited without the presence of 3C-SiC inclusions or polycrystalline SiC, as observed by defect selective etching, scanning electron microscopy and optical microscopy. Large defect free areas, [similar to]5 mm[superscript]2, with epitaxial film thicknesses of [similar to]6 [Mu]m were grown on on-axis 4H-SiC. Epitaxial films had approximately an 80%, [similar to]20 cm[superscript]-2, decrease in defect density as compared to the substrates. The growth rate was independent of face polarity and orientation of the substrate. The optimal temperature for hydrogen etching, to promote the smoothest epitaxial films for on-axis substrates (both C- and Si-polarities), is [similar to]1550 °C for 10 minutes in the presence of 2 slm hydrogen. The optimum C/Si ratio for epitaxial growth on on-axis 4H-SiC is 1; excess carbon resulted in the codeposition of graphite and cone-shaped silicon carbide defects.
Keywords: Silicon carbide; Chemical vapor deposition; Homoepitaxy; On-axis; Engineering, Chemical (0542); Engineering, Materials Science (0794)